Enthalpy of melting of α′- and α-crystals of poly(l-lactic acid). (September 2015) - Righetti, Maria Cristina; Gazzano, Massimo; Di Lorenzo, Maria Laura; Androsch, René
Graphical abstract: Highlights: The temperature-dependence of Δ hm ° of α′- and α-crystals of PLLA is determined. α′- and α-crystals of PLLA have different melting enthalpy. At the melting temperature, Δ hm ° of the α′-form is 107 J g −1 . At the melting temperature, Δ hm ° of the α-form is 143 J g −1 . The lower Δ hm ° value of the α′-form is linked to conformational defects. Abstract: Literature values of the enthalpy of melting (Δ hm °) of 100% crystalline poly(l -lactic acid) (PLLA) vary in a wide range (82–203 J g –1 ). In most cases, such values were determined without taking into account the presence of α′- or α-crystal modifications, or the influence of d -lactic acid units in the analyzed poly(lactic acid). The bulk enthalpy of melting was determined for the stable orthorhombic α form in only few studies, and thermodynamic properties of the metastable α′-modification are not available yet. In the present work, the temperature dependence of Δ hm ° for both the α′- and α-crystal polymorphs of PLLA are determined, by combining differential scanning calorimetry and X-ray diffraction. It is proven that the enthalpies of melting of α′- and α-crystals of 100% crystalline PLLA are different. At the respective melting temperatures of 150 °C and 180 °C, the Δ hm ° values of the α′- and α-forms are 107 and 143 J g −1 . At identical temperature, the enthalpy of melting of α′-crystals is approximately 25 J g −1 lower than that of the α-form. This observation is rationalized taking into account the presence of conformational defects in the disordered α′-modification.